2010
DOI: 10.5137/1019-5149.jtn.3146-10.0
|View full text |Cite
|
Sign up to set email alerts
|

Stereological evaluation of temporal lobe / telencephalon volume in temporal lobe epilepsy using cavalieri principle

Abstract: AIM:Epilepsy is a temporary electric discharge in the brain cells due to shortterm brain function disorder. Epileptic seizures mostly stem from the temporal lobe. The prevalence is the same for women and men. It is thought that there are both microscopic-and macroscopic-level localized changes in the temporal lobe epilepsy. This study aims to assess the volumetric changes that might occur in temporal lobe epilepsy and compare these with normal brains. MATERIAL and METHODS: Volumetric assessment of temporal lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…Bunun yanı sıra epileptik nöbetler beyinde birçok bölgede nöronal kayıplara ve dejenerasyonlara sebep olur. [3,12] Özellikle görüntüleme yöntemlerinin gelişmesi ile birlikte epilepside nöronal etkilenme ve etiyolojide rol alan etmenler daha iyi anlaşılmaya başlanmıştır. [3,13,14] KK, miyelin liflerinden oluşan ve her iki serebral hemisferi birbirine bağlayan interhemisferik bir yoldur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bunun yanı sıra epileptik nöbetler beyinde birçok bölgede nöronal kayıplara ve dejenerasyonlara sebep olur. [3,12] Özellikle görüntüleme yöntemlerinin gelişmesi ile birlikte epilepside nöronal etkilenme ve etiyolojide rol alan etmenler daha iyi anlaşılmaya başlanmıştır. [3,13,14] KK, miyelin liflerinden oluşan ve her iki serebral hemisferi birbirine bağlayan interhemisferik bir yoldur.…”
Section: Discussionunclassified
“…[2] Ayrıca bu yapısal değişim süreci çevresel faktörler ve hastalığın nöropatolojik süreci ile ilişkidir. [1][2][3] Manyetik rezonans görüntüleme (MRG) ve bilgisayarlı tomografi (BT) gibi görüntüleme teknikleri epilepsi, demans gibi hastalıklarda beynin yapısal değişimlerini incelemeye olanak sağlar. [1,2] Özellikle MRG araştırmaları bu değişiklikleri göstermede daha değerlidir.…”
Section: Introductionunclassified
“…Scientists are attempting to find new methods of processing and storing these images. Additionally, changes in cortical structures can be determined using a planimetry method, which is considered the golden standard 2,3,6,12. The CC, which is composed of myelin fibers, is the primary cause for a generalization of seizures generated by an epileptogenic focus.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that TLE is a disorder of abnormal epileptogenic networks, rather than focal sources 2. The relationship between the cortical brain structure with neuropsychological and neurophysiological events cannot be completely explained 3. The corpus callosum (CC) is the most important tract between cortical brain structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation